RELATIONSHIP BETWEEN DURATION AND REGULARITY OF MENSTRUAL CYCLE WITH PRIMARY DYSMENORRHEA IN ADOLESCENTS - Risda zairina; Budi Utomo (UNIVERSITAS AIRLANGGA, 2023)
Background: For women who have experienced menstruation, some common problems can occur such as pain during menstruation or disturbances in the menstrual cycle. The high prevalence of primary dysmenorrhea requires appropriate prevention and treatment efforts by recognizing the risk factors for primary dysmenorrhea, one of which is an abnormal menstrual cycle. Based on the existing literature, this study aims to examine the relationship between the length and regularity of the menstrual cycle with the incidence of primary dysmenorrhea. Method: This type of research is quantitative with cross sectional design. The minimum number of samples used is 57 people who are determined by the simple random sampling technique. The data collection instrument in this study was a questionnaire in the form of a Google form. The independent variables in this study were the length and regularity of menstrual cycle and the dependent variable was primary dysmenorrhea. The statistical tests used were Spearman Rank and Exact Fisher's Test with a significance value (P) = 0.05 to determine the level of significance of the research results. Results: Based on the results of the Spearman Rank statistical test, a significance value of 0.3 was obtained where the value of Sig.(2-tailed) > 0.05, so it was concluded that there was no relationship between the length of the menstrual cycle and the incidence of primary dysmenorrhea. The results of the Exact Fisher's Test obtained a significance value of 0.034 where the value of Sig.(2-sided) <0.05, it was concluded that there was a significant relationship between the regularity of the menstrual cycle and the incidence of primary dysmenorrhea. Conclusion: There is no relationship between the length of the menstrual cycle and the incidence of primary dysmenorrhea and there is a relationship between the regularity of the menstrual cycle and the incidence of primary dysmenorrhea. Key words : menstrual cycle, primary dysmenorrhea, adolescents